Evaluation of The Implementation of The Inclusion Program - Rokhim, Abdul; Suryadi, Suryadi; Supadi, Supadi (Universitas Pendidikan Ganesha, 2021)
In practice, inclusive schools face many obstacles, using a curriculum that has not been fully implemented properly. Teachers do not understand using methods and learning media for children with special needs. Be in a good instrument. Unique infrastructure that has not been adequate in supporting child development is an obstacle to implementing inclusive education successfully. This study aims to analyze the Inclusive Education program's context, inputs, processes, and products. This research is a program evaluation research using the CIPP model. The methodology used is a survey and descriptive method. The research informants were the principal, vice-principal for curriculum and student affairs, teachers, special assistant teachers data collection techniques through observation, questionnaires, and interviews. The technique used to analyze power is descriptive qualitative analysis. Based on the data, the problem with inclusive education programs experienced by schools is the presence of non-permanent accompanying teachers who only receive one time per week, thus hampering the development of students with special needs. In addition, the facilities and infrastructure that support the learning process are still incomplete. The uniqueness of the inclusive education curriculum needs to be reviewed to improve children's learning abilities with special needs.